If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + 3 = 4y Combine like terms: 3 + 3 = 6 6 = 4y Solving 6 = 4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4y' to each side of the equation. 6 + -4y = 4y + -4y Combine like terms: 4y + -4y = 0 6 + -4y = 0 Add '-6' to each side of the equation. 6 + -6 + -4y = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -4y = 0 + -6 -4y = 0 + -6 Combine like terms: 0 + -6 = -6 -4y = -6 Divide each side by '-4'. y = 1.5 Simplifying y = 1.5
| x^4+4x^3-448=0 | | 5/5+3/4 | | 0=x^2-8x+10 | | 2x=0.6 | | r+7=19 | | 1.3(z)+1.5=5.4 | | 7(x+2)+2(-3+2x)=x+6 | | -4X^2-3=0 | | 16x^2-5x-17=0 | | 1.3(7)+1.5=5.4 | | -3-4(n+8)=10-4n | | .04x=1.2 | | 10+64n^2=59 | | -4X^2=3 | | 12x-(x-1)= | | 3(p+6)=-2(3p+5)+1 | | 0.2(m)-7=3 | | (6t+9)(6t+9)=14 | | -3-9x^2=-444 | | 14p+7=35 | | 5x^2+5x+8=0 | | .3333=n+1.3333 | | 5r^2-245=0 | | 70000-38741= | | (6t+9)2=14 | | 2w+7w-14=58 | | 12y^2+5y+8=0 | | 14x^2+35x-2=-2 | | 4(4-4x)= | | 6(1-6x)=6(x-6) | | .16(4x-8)=6x | | X=96+.3x |